(untitled) (Fiep Bulletin - online, 2016)
Cultural society in general understands that the Physical Education classes are the time to play, play and train physical. Students of the 5th year of elementary school II EMEF Antonio de Alcantara Machado understand that study is part of the daily school physical education learning interesting things and apply on a daily basis. The chewing was the theme of classroom chosen to develop with the students, considering the ignorance on the part of them about this movement is so important for our quality of life. The purpose of this paper is to report the experience of the knowledge of the chew to the daily lives of students.